Predictive value of modified systemic inflammation score for postoperative unplanned ICU admission in patients with NSCLC - Wang, Zhulin; Zhang, Hua; Huang, Chunyao; Li, Kaiyuan; Luo, Wenqing; Zhang, Guoqing; Li, Xiangnan (Frontiers in Surgery, 2022)
Background: The purpose of this study was to investigate the predictive value of the modified systemic inflammation score (mSIS) in postoperative unplanned admission to the intensive care unit (ICU) in patients with non-small-cell lung cancer (NSCLC). Methods: The clinical data of 1321 patients with NSCLC treated with thoracic surgery in our hospital from August 2019 to June 2021 were analyzed retrospectively. The preoperative mSIS score, which takes into account the serum albumin (ALB) level and lymphocyte-to-monocyte ratio (LMR), was recorded as 0,1 or 2 and then was used to identify high-risk patients with unplanned admission to the intensive care unit (ICU). The independent risk factors for unplanned admission to the ICU in patients with NSCLC after surgery were identified by multivariate logistic regression analysis. Results: A total of 1321 patients, including 549 (41.6%) males and 772 (58.4%) females, were included. The median age was 57 years (range 16-95 years). The incidence of unplanned admission to the ICU in patients with mSIS=2 was significantly higher than that in those with mSIS=0 and mSIS=1. The multivariate analysis showed that a mSIS of 2 (OR=3.728; p=0.004; 95% CI, 1.520-9.143), an alcohol consumption history (OR=2.791, p=0.011; 95% CI, 1.262-6.171), intraoperative infusion volume (OR=1.001, p=0.021; 95% CI, 1.000-1.001) and preoperative underlying diseases (OR=3. 57, p=0.004; 95% CI, 1.497-8.552) were independent risk factors for unplanned admission to the ICU after lung cancer surgery. In addition, the multivariate logistic regression model showed that the C-statistic value was 0.799 (95% CI 0.726 ~ 0.872 P < 0.001). Conclusions: The mSIS scoring system can be used as a simplified and effective predictive tool for unplanned ICU admission in patients with NSCLC.